Teaching reading in high school English classes - Ericson, Bonnie O. (Urbana, IL : National Council of Teachers of English, 2001)
Contains ten essays that offer suggestions to teachers on how to teach reading in high school English classes, addressing the varying needs for reading instruction among high school students.
"NCTE stock number: 51868-3050"--T.p. verso.
Includes bibliographical references.
Voice of Youth Advocates (V.O.Y.A.).
Professional
Keywords: Literature -- Study and teaching (Secondary) -- United States; Reading (Secondary) -- United States; Literature -- Study and teaching; Reading